Unraveling deep roots in drylands: a systems thinking participatory approach to SDGs - Ana Paula Dutra Aguiar; David Collste; Sofia Cortés-Calderón; Taís Sonetti-González; Minella Alves-Martins; Antonio J. Castro; Amadou Diallo; Karl Martin Eriksson; Deborah Goffner; Zuzana V. Harmáčková; Amanda Jiménez-Aceituno; María D. López-Rodríguez; et al. (Global Sustainability)
Abstract Non-technical summary Achieving sustainability on the ground poses a challenge in decoding globally defined goals, such as sustainable development goals, and aligning them with local perspectives and realities. This decoding necessitates the understanding of the multifaceted dimensions of the sustainability challenges in a given context, including their underlying causes. In case studies from Brazilian drylands, we illustrate how an enhanced multiscale participatory method, combined with systems thinking tools, can shed light on systemic structures that currently entrench unsustainable development trajectories. This method offers insights into co-designing potential pathways toward sustainable futures and unlocking transformative capacities of the local population.